Factors Controlling the Development of Wine-Glass Forms in the Mountains of the Kurdistan Region, Iraq - Sissakian, Varoujan K.; Othman, Arsalan A.; Shihab, Ahmed T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
The northern and northeastern parts of Iraq are mountainous areas and rugged topography with different erosional and morphological forms; among them are the wine-glass (erosional cirques) forms. They are developed in different shapes, sizes, and depths. In the outlets of the wine-glass forms; usually, alluvial fans are formed. The studied area is characterized by the presence of long and narrow anticlines with NW–SE trend that changes westward to E–W trend. The Cretaceous carbonate rocks form the main carapace of the majority of the mountains; however, locally Paleogene and/or Jurassic rocks form the carapace. In the core, rocks down to Devonian are exposed. In those anticlines where only Cretaceous rocks are exposed, no or very rarely wine-glass forms are developed. This is attributed to the Cretaceous carbonate rocks, which exist in huge thicknesses in many formations, with thickly bedded to massive nature and very hard erosion resisting rocks. Tens of the existing wineglass forms are studied to indicate the factors that control their development, which are the type of exposed rocks, their thicknesses, and hardness. To perform the aim of this study, different satellite imagery with different resolutions was used; besides using GIS technique and field check to improve the acquired date.